Comparative studies of dynamic hysteresis responses in hard and soft PZT ceramics - N. Wongdamnern (2018)
Lead zirconate titanate (PZT) is a ferroelectric material with very interesting and useful dynamic hysteresis properties. Normally, PZT is doped with donors or acceptors to yield better electrical properties. Soft and hard PZT ceramics are respectively donor- and acceptor-doped PZT, which are commercially available and widely employed in various applications. Previous investigations have mainly been focused on the dynamic hysteresis at room temperature and under stress-free condition. However, when used, these ceramics are normally subjected to stress. More importantly, the ambient temperature is usually not at room temperature. Therefore, this study was to investigate dynamic hysteresis behavior of both hard and soft PZT ceramics with varying compressive stress and temperature. The results clearly revealed the influence of external stress and temperature on the dynamic hysteresis of both types of PZT ceramics. Increasing stress and temperature resulted in a decrease of the hysteresis area of the two types of PZT ceramics. © 2007 Elsevier Ltd and Techna Group S.r.l.